2015
DOI: 10.4103/0970-9290.167629
|View full text |Cite
|
Sign up to set email alerts
|

Flapless versus open flap techniques of implant placement: A 15-month follow-up study

Abstract: Both techniques showed a reduction in CBH with time but the flapless technique showed a lesser reduction. Therefore, the flapless technique can be considered as a better treatment approach for placement of implants, especially where adequate width and height of available bone are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The insertion torque value in this study showed broader (10 to 50 N cm) than the previous publication (Table 2 ) [ 22 , 32 ], and the cause of reasons for the difference are as follows: Primary stability may be affected by the bone quantity and bone quality in the treatment area, the micro- and macro-level design of the implant body, and the accuracy of the surgical technique [ 18 , 25 ]. In this study, the 17 dentists performed implant treatment.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The insertion torque value in this study showed broader (10 to 50 N cm) than the previous publication (Table 2 ) [ 22 , 32 ], and the cause of reasons for the difference are as follows: Primary stability may be affected by the bone quantity and bone quality in the treatment area, the micro- and macro-level design of the implant body, and the accuracy of the surgical technique [ 18 , 25 ]. In this study, the 17 dentists performed implant treatment.…”
Section: Discussionmentioning
confidence: 57%
“…All numerical data obtained in this research were statistically analyzed with one-way analysis of variance and multiple comparison tests by Bonferroni et al [ 22 ]. Fisher’s exact test and the corresponding t test were used for statistical analysis of insertion torque values and the relationship between ISQ and insertion torque, respectively [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various factors that influence the success and failure of any implant rehabilitation are the type of surgical technique, primary implant stability, and volume and quality of bone around the implant. [ 23 ] One hundred percent survival rate of solitary implants after 1 year was depicted in the results of this study regardless of the surgical technique. This is comparable with other clinical trials which depicted equal survival rates of both flapless and flap surgery groups.…”
Section: Discussionmentioning
confidence: 65%
“…Few authors have advocated that placing implants with a minimally invasive technique not only reduced the trauma but also maintains the tissue volume. [ 21 - 23 ] Cannizzaro et al . [ 14 ] have greatly emphasized the benefits of the flapless technique in terms of minimal trauma and better acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…And in the flapless technique, bone vascularization is preserved. Once the periosteum is stripped, there is a definite loss of blood supply to the crestal bone leading to increased bone loss which is found in the flap technique [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%